Exercise stress echocardiography: Impact on clinical decision‐making in pediatric patients. Issue 5 (1st April 2019) - Dasgupta, Soham; Friedman, Heather; Allen, Nicole; Stark, Megan; Ferguson, Eric; Sachdeva, Ritu; Border, William L.
Abstract : Background: The role of exercise stress echocardiography (ESE) in the pediatric population is less well defined as compared to adults. We aimed to determine the utility and impact of ESE on clinical decision‐making in pediatric patients. Methods: We identified patients who underwent an ESE at our center from 2011 to 2015. Test indications were categorized into symptoms with exercise; sports/activity clearance; hypertrophic cardiomyopathy (HCM) or suspected HCM; coronary anomalies; or abnormal electrocardiogram (EKG). Change in clinical management was assessed by comparing pre‐ and post‐test activity restrictions, which were categorized into unrestricted from exercise or activity; restricted from exercise or activity; and surgical referral. Results: During the study period, 353 ESEs met inclusion criteria. Of all ESEs performed, 263 (75%) were normal. Clinical management changed as a result of ESE in 144 (40%). Of the abnormal ESEs, 44 were restricted from activity, including 25 (56.8%) restricted from competitive or varsity athletics, 14 (31.8%) restricted from recreational sports, and 5 (11.4%) restricted from all activity. Surgical referrals included valve repair/replacement in 7 (50%), ICD placement in 5 (35.8%), coronary re‐implantation in 1 (7.1%), and atrial septal defect repair in 1 (7.1%). Conclusion: Exercise stress echocardiography provides the pediatric cardiologist with useful information that impacts management in a wide variety of cardiac disorders. Clinical management changed in nearly half the patients that were subjected to an ESE at our center. This supports the value of ESE for informing clinical decision‐making. Future studies should aim to refine patient selection and examine its impact on patient outcomes.